Molecular Structure Profiles of Major Chemical Components of Vernonia amygdalina and Tephrosia vogelii Leaf Extracts - Olunga, M. S.; Wanjala , F. M. E.; Mburu , F.; Ngeiywa , M. M.; Sirma , P.; Siamba , D. N. (African Journal of Education,Science and Technology (AJEST), 2013)
Plants contain various chemical components some of which play vital roles in the bodies of plants and animals. It is essential that the chemical composition of these plants be well elucidated in o rder to come up with their mode of action. The objective of this study was to determine the major chemical constituent of Vernonia amygdalina and Tephrosia vogelii leaf extracts and elucidate the molecular structure profiles of the chemical components. Mature leaves were collected from Kenya Agriculture Research institute (KARI) Naivasha. Collection was done during two peak seasons, dry season February and wet season April. Chemical analysis involved determination of chemical extractive content of the plant leaves; the crude extract of the plants was obtained by Soxhlet extraction using the different solvents comprising of hexane, ethyl acetate, methanol, toluene/ethanol (2/1 v/v) mixture and water, followed by characterisation of the plant extracts by Nuclear Magnetic Resonance (1H 13C NMR), Fourier-Infra red Analysis (FTIR) and Gas Chromatography Mass Spectrometry (GC-MS). Assays for Chemical Constituents and compound identification were based on National Institute of Standards and Technology (NIST) library. The major secondary metabolites detected in all plants were glycosides, whereas, tannins and rotenoids were detected in Tephrosia only. A higher amount of these compounds were observed during the dry season compared to the wet season. This could be attributed to the increase in maturation of leaves during the dry season. Sesquiterpene lactones were on the other hand detected only in Vernonia during both the wet and dry season at the same amounts.